Inclusive Education Practices in Australia (Victoria) and Pakistan: Readiness of School Education System, Teachers’ Training, Pedagogy, Curriculum and Assessment - Fauzia Khurshid; Farooq, Muhammad Shahid (JIE, 2025)
This research compared inclusive teaching practices in Pakistan and Australia, focusing on early interventions, pre- and in-service teacher training, inclusive curriculum and pedagogy, assistive device provision and assessment methods for learners with disabilities and special needs. A qualitative analysis, using structured interviews, explored the current state of inclusive education practices in both countries. In Australia, education is primarily a government responsibility and inclusion are systematically integrated into all school systems. This is supported by policies, legislation and guiding documents. While separate schools exist for children with specific learning needs and disabilities, the overall approach is to welcome and support all learners, without discrimination, in mainstream schools, enabling them to reach their full potential. In Pakistan, inclusive education practices are currently hindered by several barriers. These include a lack of support and vision for understanding the importance of inclusion, insufficient resources for training teachers and allied staff and a general lack of preparedness among mainstream teachers for pedagogy and assessment in the mainstream setting. The research highlights the urgent need to transform the existing mainstream school system by allocating adequate financial and physical resources so a workable model could be developed to promote inclusive practices in the mainstream schools. Findings will create a foundation for inclusion, allowing schools to effectively welcome and support children with special needs and disabilities on the analogy of Australia.